Accumulated effects of factors determining plant development from somatic embryos of Abies nordmanniana and Abies bornmuelleriana - Nielsen, Ulrik Braüner; Hansen, Camilla Bülow; Hansen, Ulrich; Johansen, Vivian Kvist; Egertsdotter, Ulrika (Frontiers in Plant Science, 2022)
Despite a much later inception of in vitro propagation protocols than for angiosperm species, somatic embryogenesis (SE) in gymnosperms is becoming increasingly important due to its applications for commercial forestry. For many conifers, there are still several major bottlenecks in the SE process limiting the use of SE for producing plants for forestry, Christmas tree production, and research projects. In the present case study, two conifer species of high value for Christmas tree production were studied throughout SE development. Seven clones of Abies nordmanniana and two clones of Abies bornmülleriana were included in the study. Accumulated effects of cultural treatments from the start of germination of 3097 mature embryos through development to growing plants were recorded. Plants from seven clones (1150 plantlets) were followed during step 1: autotrophic plant growth for 8 weeks at 15⁰C under LED light 50-400 µmol m-2 s-1 (24h) followed by step 2: establishment ex vitro in peat plugs and growth for 8 weeks at 25⁰C under LED light 200 µmol m-2 s-1 (24h), and finally step 3: three years of ex vitro growth in a commercial nursery without additional light source. The results reveal the relative importance of clonal identity, morphology of mature embryos prior to germination, germination temperature and germinant characteristics for the growth in the first three years ex vitro. Optimum germination occurred at 4⁰C. Initial embryo quality significantly influenced germination as well as 3-year plant survival. Week of germination influenced 3-year height growth and nursery survival. The case study highlights and quantifies the strong interrelation between the developmental process steps of somatic embryogenesis. The results show the importance of considering all steps of the SE process as a prerequisite to optimize SE plant production.